2020
DOI: 10.1007/s00431-020-03571-1
|View full text |Cite
|
Sign up to set email alerts
|

How do pediatric patients perceive adverse drug events of anticonvulsant drugs? A survey

Abstract: Anticonvulsant drugs have a high risk of adverse drug events. Little is known about the perception of those events by pediatric patients. We performed a survey in the neuropediatric departments of two university hospitals. Using a questionnaire, we interviewed patients aged 6-18 years with current anticonvulsant treatment regarding (i) their fears about potential adverse drug events, (ii) experienced adverse drug events, and (iii) perceived burden of experienced adverse drug events. One hundred patients took p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
2
9
0
3
Order By: Relevance
“…Preferences of children and parents concerning drug formulations differed in around half of the reports. Our ndings are in line with earlier studies that have shown that children are indeed well able to express experiences and expectations concerning their drug therapy [10,22]. Nevertheless, physicians tend to talk to the parents when they aim at exploring the children's needs.…”
Section: Expectations Of the Ideal Pediatric Drug (Part B)supporting
confidence: 90%
“…Preferences of children and parents concerning drug formulations differed in around half of the reports. Our ndings are in line with earlier studies that have shown that children are indeed well able to express experiences and expectations concerning their drug therapy [10,22]. Nevertheless, physicians tend to talk to the parents when they aim at exploring the children's needs.…”
Section: Expectations Of the Ideal Pediatric Drug (Part B)supporting
confidence: 90%
“…With regard to ADRs, it is important before treatment initiation to consider which ADRs may occur and to choose the anti-seizure medication that best meets the needs of the patients. For example, psychiatric and neurologic ADRs were judged by pediatric patients and their parents to negatively affect peer interaction and school/leisure activities [ 9 , 10 ]. Paying more attention to these patient-specific perceptions when selecting drug therapy might help to prevent discontinuation of drug therapy or change of active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was based on researches on patients’ perceptions on adverse drug reactions [ 9 , 10 ]. In this research, some points remained open that can only be answered by considering the physician’s perspective.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations